2019
DOI: 10.3892/ol.2019.10233
|View full text |Cite
|
Sign up to set email alerts
|

miR‑152 may function as an early diagnostic and prognostic biomarker in patients with cervical intraepithelial neoplasia and patients with cervical cancer

Abstract: Previous studies have demonstrated that circulating miRNAs are effective biomarkers of various types of cancer. It has also been indicated that miR-152 is upregulated in cervical cancer. However, whether miR-152 may be used as an early detection method for patients with cervical cancer is yet to be elucidated. The results of the current study demonstrated that miR-152 levels were the lowest in healthy controls, high in patients with cervical intraepithelial neoplasia (CIN), and the highest in patients with cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 34 publications
2
22
0
Order By: Relevance
“…Chen et al ( 14 ) reported that miR-499a promotes the proliferation, cell cycle progres-sion, colony formation, migration and invasion of CC cells by targeting SRY-box transcription factor 6. In addition, several miRNAs serve as diagnostic biomarkers in patients with CC, such as miR-152 and miR-365 ( 15 , 16 ). Despite the aforementioned findings, the roles of miRNAs in the development of CC require further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al ( 14 ) reported that miR-499a promotes the proliferation, cell cycle progres-sion, colony formation, migration and invasion of CC cells by targeting SRY-box transcription factor 6. In addition, several miRNAs serve as diagnostic biomarkers in patients with CC, such as miR-152 and miR-365 ( 15 , 16 ). Despite the aforementioned findings, the roles of miRNAs in the development of CC require further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Wei et al [8] reported that miR-221-3p promoted CC metastasis by directly targeting twist homolog 2 (TWIST2). Additionally, some miRNAs, such as miR-365 and miR-152, have become potential diagnostic biomarkers in patients with CC [12,13]. Therefore, identifying more miRNAs that are aberrantly expressed in CC and addressed their underlying molecular mechanisms can be beneficial for therapeutic approaches for CC.…”
Section: Introductionmentioning
confidence: 99%
“…miR-153 has been previously reported to regulate radiosensitivity ( 8 , 9 ), as well as other processes, in various types of cancer. For example, miR-153 was reported to mediate cell proliferation and apoptosis in renal cancer ( 13 ), inhibit migration in breast ( 14 , 15 ) and lung cancer ( 16 ), act as a prognostic marker for gastric ( 17 ) and cervical cancer ( 18 ), mediate immune escape from natural killer cells in pancreatic cancer ( 19 ), and enhance chimeric antigen receptor T cell immunotherapy in colon cancer ( 20 ). In pancreatic cancer, miR-153 mainly has antitumour properties.…”
Section: Discussionmentioning
confidence: 99%